Ações Públicas para o Desenvolvimento Rural Sustentável dos Ambientes de Montanha Brasileiros - Amazile López Netto (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2017)
Brazil is among the twenty countries with largest area of mountains on the planet and fourth among the countries of Latin America. The mountain environments have particular characteristics due to interaction "altitude – height – slope", wealth in water resources, difficult access, among others. The purpose of this paper was to reflect specific public actions for sustainable rural development in mountain environments in Brazil, which was conducted through a literature review. The reality of the Brazilian mountain environments is not contemplated, applying the same policy to the highlands and the lowlands. Policies in mountain environments are directed to cross-cutting themes such as rural tourism, agroforestry and payment for environmental services.